The Influence of Work Conflict, Workload and Work Environment on Performance Among Outsourced Hospital Employees - Nurcahyo, Indra; Syahputra, Erwin; Saputra, Beny Mahyudi; Dewi, Anita Sumelvia (Transpublika Publisher, 2025)
Outsourced healthcare employees encounter specific obstacles that can have a substantial influence on their performance, such as work conflicts, high workloads, and unsatisfactory working conditions. Understanding these aspects is critical for healthcare management in order to provide quality services and maintain employee well-being. This study delves into the impact of work conflict, workload, and work environment on the productivity of contracted workers at Bhayangkara Hospital in Kediri. The research evaluates work conflict (X1), workload (X2), and work environment (X3) as factors that can affect the performance of employees, with employee performance (Y) being the key variable under consideration. A quantitative approach was employed, utilizing interviews, observations, literature review, and questionnaires for data collection. The analytical methods included validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, f-tests, and determination coefficient analysis. The research used a saturated sampling technique, encompassing all 96 non-medical outsourcing employees at Bhayangkara Hospital, Kediri. The analysis suggests that the workload factor has a significant impact on employees' performance, with a significance level of 0.041, which is less than 0.05. Similarly, the workload variable also has a notable influence, with a significance level of 0.000, still less than 0.05. Additionally, the work environment component plays a significant role in affecting employee performance, with a significance level of 0.038, below the 0.05 threshold.